Effect of some exercises and helpful tools to develop some specific physical capability in javelin (Experimental Research) On sample of, College of sport L University of Baghdad - Shaghati, Ahlam (Journal of Physical Education, 2015)
The importance of the research is during the effect of the track and field class on the development of performance. The program of the class needs to use helpful tools with the physical components for each efficiency in order to reach good performance in javelin. The research problem is during lack of use helpful tools and girl student physical weakness in the javelin. The aim of the research is to identify the effect of exercises and the helpful tools to develop physical fitness in javelin. Prepare same exercises using same tools to develop special abilities in javelin throw for girls in college of physical and sport sciences. The hypotheses the research: The helpful tools make objective in the development of some physical fitness components in javelin. There are significant differences between P&E and post tests for both groups and There are significant differences between experimental and control group in posttests